2017
DOI: 10.1186/s13054-017-1730-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled pilot study to evaluate the effect of an enteral formulation designed to improve gastrointestinal tolerance in the critically ill patient—the SPIRIT trial

Abstract: BackgroundDiarrhea is frequent in patients in intensive care units (ICU) and is associated with discomfort and complications and may increase the length of stay and nursing workload.MethodsThis was a prospective, double-blind, randomized, controlled single-center pilot study to assess the incidence and frequency of diarrhea and the respective effects of a modified enteral diet (intervention: Peptamen® AF, rich in proteins, medium chain triglycerides and fish oil) compared to a standard diet (control: Isosource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 32 publications
1
47
0
5
Order By: Relevance
“…Six trials were eligible for inclusion, which included 511 patients ( Figure 1, PRISMA diagram). [27][28][29][30][31][32]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six trials were eligible for inclusion, which included 511 patients ( Figure 1, PRISMA diagram). [27][28][29][30][31][32]…”
Section: Resultsmentioning
confidence: 99%
“…For continuous variables, mean and SD were directly recorded, and median with interquartile range data were converted prior to analysis to approximate mean (SD) data as described by Wan et al 26 All included studies reported protein and energy provision in g/kg per day and kcal/kg per day; when actual weight was reported and the mean BMI was within the healthy weight range (BMI 18.5-25 kg/m 2 if ࣘ65 years old, 22-27 kg/m 2 if >65 years old), the reported mean (SD) protein dose was used in data analyses; if actual weight was reported and the mean BMI was above the healthy weight range, then calculations were done to assess the protein provision based on IBW (defined as the upper end of the healthy weight range); if studies reported IBW or an adjusted IBW for the protein dose, this was used in the data analyses. One author was contacted 27 to further assess their data to confirm that protein was provided at a level of 1.2 g/kg IBW per day in the intervention.…”
Section: Data Handling and Statistical Analysismentioning
confidence: 99%
“…All patients were managed by targeted, light sedation and protocol-guided weaning [23]. Standard ICU care also included a nutrition protocol and regular assessments of energy expenditure using indirect calorimetry [24]. Physiotherapy started within 48 hours of ICU admission with two different exercise regimes that included usual early mobilisation versus early, progressive endurance and resistance training in addition to usual early mobilisation.…”
Section: Study Population and Managementmentioning
confidence: 99%
“…In der sog. Spirit-Studie führte der Einsatz einer enteralen Diät mit hydrolysiertem Protein verglichen mit einer polymeren Standardsondenkost nicht zu einer Verringerung diarrhöfreier Tage [227]. Zum Einsatz von Ballaststoffen wird auf Kap.…”
Section: Empfehlung 34bunclassified